Status Identitas Etnik pada Mahasiswa Etnik Sunda dan Cina - Sanusi Soesanto (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2006)
This study aimed to get description of the Ethnic Identity Status of Sundanese and Chinese ethnic background at Maranatha Christian University in Bandung. 49 students from Sundanese ethnicity and 98 students Chinese ethnicity are chosen as sample. Phinney’s Ethic Identity Status interview are used to collect data while, Chi Quadrate are used to analyses the data. Result show that is a difference (Chi square X2 = 4.930; a = 0.01) between the ethnic identity status of Sundanese and Chinese Ethnic Students. The two group have a low percentage on Achieved Ethnic Identity. Sundanese students have higher percentage on Foreclosure Ethnic Identity (57.14 %) while students of Chinese ethnicity have a higher percentage on Moratorium (Ethnic Identity Search = 58.16%).Key words: Ethnic Identity Status; Identity Achieved, Moratorium, Foreclosure, and Diffusion.